Open innovation as the missing link in the mediated model among R&D educational heterogeneity, innovation and performance - Fabijan Leskovec; Matej Černe; Darja Peljhan (Journal of Innovation & Knowledge)
This study examines the interrelationships between the educational structure of the research and development (R&D) department, open innovation, innovativeness and organisational performance. The main purpose of the article is to help companies establish successful R&D as one of the determinants of organisational performance, and to explore the underlying processes and boundary conditions of this relationship. Based on the theoretical background of R&D management, cognitive diversity, and open innovation, we hypothesise that R&D educational heterogeneity is positively related to organisational performance via innovativeness, which is moderated by firms' open innovation. We collected data from 151 organisations based in Slovenia, Austria, and Croatia. We analysed the data with (moderated) mediation procedures. Our findings support the hypotheses, except for the direct relationship between R&D education heterogeneity and organisational performance, and confirm our expectations regarding the high importance of innovativeness as a mediator of this relationship. Furthermore, our findings are consistent with theoretical assumptions that group and R&D diversity and open innovation interplay in predicting innovativeness and ultimately firm performance. Our findings provide new perspectives on R&D, particularly on the educational structure of R&D employees and its interaction with open innovation in relation to organisational performance.